1993
DOI: 10.1111/j.1476-5381.1993.tb13557.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of chronic treatment with nitric oxide synthase inhibitors on regional haemodynamic responses to vasodilators in conscious Brattleboro rats

Abstract: 1 The effects of acute inhibition of nitric oxide (NO) synthase on cardiovascular responses to vasodilator challenges have already been described. We now report the responses to vasodilators during and after chronic NO synthase inhibition. 2 In conscious Brattleboro rats, the regional haemodynamic effects of 3 min infusions of acetylcholine (4 g min-'), sodium nitroprusside (15 fg min ') or adrenaline (0.2 ig min-') were assessed (from areas under or over curves (AUC, AOC)) under control conditions, 6 and 72 h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
6
1

Year Published

1994
1994
2003
2003

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 14 publications
1
6
1
Order By: Relevance
“…This suggests that within the kidney vasculature, vasodilatation induced by acetylcholine is mediated by mechanisms in addition to NO, as there is no evidence that eNOS varies between endothelial cells in different portions of the vasculature. This conclusion would be consistent with other studies that havi found L-NAME to be ineffective at inhibiting the acetylcholine renal vasodilatation in vivo as well as the acetylcholine hypotensive response (Gardiner et al, 1990b), althougb long term exposure to L-NAME has been associated with an attenuation of the renal vasodilator effects of acetylcholine in vivo (Gardiner et al, 1993). There are a number of possible explanations for this relative resistance to the effects of eNOS inhibition.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…This suggests that within the kidney vasculature, vasodilatation induced by acetylcholine is mediated by mechanisms in addition to NO, as there is no evidence that eNOS varies between endothelial cells in different portions of the vasculature. This conclusion would be consistent with other studies that havi found L-NAME to be ineffective at inhibiting the acetylcholine renal vasodilatation in vivo as well as the acetylcholine hypotensive response (Gardiner et al, 1990b), althougb long term exposure to L-NAME has been associated with an attenuation of the renal vasodilator effects of acetylcholine in vivo (Gardiner et al, 1993). There are a number of possible explanations for this relative resistance to the effects of eNOS inhibition.…”
Section: Discussionsupporting
confidence: 90%
“…This suggestion is supported by our finding of an enhanced response in vivo to sodium nitroprusside after chronic treatment with L-NAME. On the other hand, we found no such enhancement in the responses of isolated perfused kidneys or thoracic aortae prepared from animals chronically exposed to L-NAME, as is the case for both changes in arterial blood pressure and regional blood flows in vivo (Arnal et al, 1992;Gardiner et al, 1993). A second explanation may be that acetylcholine stimulates, in addition to NO, the release of endothelium-derived vasodilators such as endothelial-derived hyperpolarizing factor (Komori et al, 1988).…”
Section: Discussioncontrasting
confidence: 52%
“…The lesser mesenteric vasodilator effect of SNP in TG rats was still apparent in the presence of L‐NAME, when there was clear sensitization to the depressor, and renal, mesenteric and hindquarters vasodilator effect of SNP in both strains of rat. If the increase in the haemodynamic effects of SNP in the presence of L‐NAME can be attributed to upregulation of the sensitivity of guanylyl cyclase to exogenous NO, when endogenous NO production is suppressed (Moncada et al , 1991; Gardiner et al , 1993a), then our results provide no evidence of an impairment of this process in TG rats.…”
Section: Discussionmentioning
confidence: 66%
“…We, and others, have previously reported increased responses to nitrovasodilators in the presence of nonselective NOS inhibition (Moncada et al ., 1991; Gardiner et al ., 1993) and this has been attributed to a supersensitivity at the level of soluble guanylyl cyclase in the absence of endogenous NO (Moncada et al ., 1991). Some augmentation of response might also be expected due to the change in baseline haemodynamic status caused by the NOS inhibitor.…”
Section: Discussionmentioning
confidence: 99%